PENGARUH MODAL INTELEKTUAL TERHADAP NILAI PERUSAHAAN STUDI KASUS PERUSAHAAN INDUSTRI TAMBANG YANG TERDAFTAR DI BURSA EFEK INDONESIA - Milda Fitriani Nainggolan; Helvoni Mahrina (Jurnal Ilmu Akuntansi, 2019)
This study aims to determine how much influence intellectual capital has on firm value. Variable intellectual capital is measured by the pulic model (1998) "Value Added Intellectual Coefficient" (VAIC ™). Company value is measured by Price Book Value (PBV). The research sample used was a mining industry company listed on the Indonesia Stock Exchange (IDX) with the study period of 2013 - 2017. Data were collected by purposive sampling method. The sample used is 19 companies each year. The research method uses the classic assumption test, multiple linear regression analysis, t test, f test and coefficient of determination. The results showed that Value added human capital had no effect on firm value, Value added capital employed had no effect on firm value and Structural capital value added had an effect on firm value.